Sustainable municipal solid waste management decision making. Issue 6 (14th September 2015) - Ak, Hacer; Braida, Washington
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to assess a comprehensive model that computes a single score in order to evaluate the sustainability of the municipal solid waste management (MSWM) system of a given city. The model was applied to calculate the sustainability index for the MSWM of Istanbul, Turkey as a case study. Design/methodology/approach – Different sustainability indicators (including environmental, economical, and social parameters) along with exergy analysis were integrated to utilize an analytical hierarchy process (AHP) under a life cycle perspective. Findings – The Istanbul case study helped to verify that AHP is an effective and efficient decision-making tool. According to the analysis, the current MSWM system of Istanbul is sustainable, and the sustainability can be improved only by changing the amounts to be treated by the current system without any new technological investments. Research limitations/implications – The Municipal Solid Waste Management Sustainability Index (MSWMSI) in this study allowed to integrate large amount of information on interrelated parameters and the sustainability indicators in the whole life cycle into one value that is useful for a general or a comparative judgment and helpful in MSWM decision making. Originality/value – The fact that the weighting assigned to each component in the model is dependent on the decision makers' evaluations enables the model to be tailored to any city of concern. The model allows the user to readily determine the relative contribution of each criterion or sub-criterion to the final MSWM selection. It is convenient to use and the computations can be run utilizing available specialized software as well as computing by hand.